Collaborative numerical simulation of hot gas flow over turbine blade using C-Denton method and comparison with Delaval nozzle. (1st January 2013) - Mohammadi, Morteza; Ziabasharhagh, Masoud; Nademi, Majid; Mohammadi, Mostafa
In this present study, dry superheated stream flow passing through turbine blade with determined configuration was investigated. Although viscosity effect can be affected on velocity and pressure, inviscid flow was taken into account because a boundary layer thickness is much smaller than turbine blade dimension. However, in order to anticipate the amount of loss occurred owing to viscosity, boundary layer effect must be completely considered. In this paper, 2D flow, unsteady inviscid gas was taken into account. It is worthwhile mentioning that after reaching to favourable convergence, steady state behaviour could be achieved and finally basic equation like continuity and momentum will be satisfied. It was proved that whenever flow reaches at leading edge of turbine blade, pressure will increase dramatically. At X/Chord = 0.95, there is a dramatic increase in Mach number which is sign of coincidence from pressure side wave to suction side wave.